A kényszermunka tilalma és a hátrányos megkülönböztetés tilalma összefüggései az Emberi Jogok Európai Bírósága esetjogában - Szemesi, Sándor (Debreceni Jogi Műhely, 2008)
The European Convention on Human Rights sets forth a number of fundamental rights and freedoms, including prohibition of slavery and forced labour (Article 4.) and the prohibition of discrimination (Article 14.). However, the European Convention on Human Rights prohibits discrimination only in relation to the enjoyment rights protected in the text of the Convention and did not originally include a provision proclaiming the equality of all before the law. As the European Court of Human Rights stated in Abdulaziz case: „Article 14 ... has no independent existence since it has effect solely in relation to „the enjoyment of the rights and freedoms” safeguarded by those provisions. Although the application of Article 14 does not necessarily presuppose a breach of those provisions - and to this extent it is autonomous -, there can be no room for its application unless the facts at issue fall within the ambit of one or more of the latter.” In this study we examine only the relationship between Article 4. and Article 14 of the Convention. There is only one case, in which the applicant could call upon Article 4 and Article 14 together with success before the European Court of Human Rights: the case of Van der Mussele versus Belgium. For this reason we introduce not only this basic case, but lots of other cases, in which there were no discrimination in connection with Article 4. The applicants should find another group of persons are in analogous situations, which worsens the position of applicants seriously because of the difficulty of this condition. In the above mentioned Van der Mussele case the applicant Belgian lawyer stated that Belgian lawyers are subject to less favourable treatment than that of members of a whole series of other professions, because in legal aid cases lawyers have to work without any remuneration, but the State accords remuneration to judges, registrars and interpreters in these cases. The Court emphasized that everybody could know the conditions of a profession in advance, and in the light of these conditions could choose it or not, and nobody compelled the applicant to be a lawyer. For this reason legal aid cases cannot be considered as forced labour, independently the remuneration of these cases.